Antioxidant/Anti-Inflammatory Potential and Sensory Acceptance of Granola Bars Developed with Sorghum Sprout Flour Irradiated with UV-A LED Light - Alan A. Ruiz-Hernández; Ofelia Rouzaud-Sández; Maribel Valenzuela-González; J. Abraham Domínguez-Avila; Gustavo A. González-Aguilar; Maribel Robles-Sánchez (Foods)
Overweight and obesity are worldwide problems; several strategies have been applied to counteract them, including the development of functional foods with specific bioactivities. Sorghum has been shown in in vitro and in vivo studies to improve various biomarkers related to overweight, obesity, and inflammation, particularly when sprouted and irradiated with UV light. In the present study, irradiated sorghum sprouts were used to prepare granola bars; their phenolic profile, antioxidant activity, in vitro bioaccessibility, anti-inflammatory potential, and sensory acceptability were measured. Gallic acid increased in response to irradiation, while catechin increased in response to sprouting. In vitro digestion showed higher intestinal recovery of phenolics and antioxidant capacity, as well as a significant decrease in nitric oxide content, an inflammation biomarker. A sensory analysis showed scores of approximately 5.5–6.5 (on a 9-point hedonic scale) for most variables analyzed, suggesting adequate acceptability. Sorghum bars made with irradiated sorghum sprouts present high potential as health foods that could help counteract the problems of overweight, obesity, and related diseases. Further in vitro and in vivo studies are needed to demonstrate the benefits of consuming this food.